Emerging Approaches to Educational Research : Tracing the Socio-Material. - Fenwick, Tara J. (Taylor & Francis, 2011)
The last fifteen years have seen much conceptual and methodological innovation in research on education and learning across the lifecourse, bringing both fresh insights and new dilemmas. This innovation was initially fuelled by the growing influence of conceptual framings often named as either post-structural or postmodern. The works of Foucault, Derrida and Lyotard have variously found their way into the canons of educational research, and in more recent years, the influence of the work of Deleuze and Guattari has also grown. This work has proved controversial both in the challenges it has ra.